(untitled) (Revista horizonte, 2014)
The cardiovascular system is mainly controlled by the autonomic nervous system (ANS) through the activity of the sympathetic and parasympathetic branches. Heart rate variability (HRV) is a noninvasive tool to evaluate this control mechanism. This review examines the different methods for evaluating the HRV, the mechanisms that underlying its control, and the responses and adaptations to different type of exercise. During the onset of a dynamic exercise, increased in heart rate is due a withdrawal of parasympathetic activity. As exercise increased in duration and / or intensity, an increment in HR is due to a gradual withdrawal of vagal activity and a concommitant increase in sympathetic activity. Immediately after exercise, the decrease in heart rate is due to a parasympathetic reactivation, with a gradual withdrawal of sympathetic activity. These variations in autonomic control of the heart can be evaluated through the HRV, although the method used will be determined by the conditions under which data are taken. In this regard, the HRV can be used to evaluate the different responses and adaptations that occur in the autonomic system. In addition, studies on HRV have shown clinical relevance, and have been linked to various diseases associated with a sympathetic-vagal imbalance. Exercise produces acute and chronic changes in the autonomic nervous system, therefore, the assessment of the HRV is very useful to obtain information about the internal load of the subjects, which would allow adjust training loads either in order to enhance sports training or for prescribing health-related exercise.